2022
DOI: 10.3390/nu14183832
|View full text |Cite
|
Sign up to set email alerts
|

Sex Difference in the Associations among Hyperuricemia with New-Onset Chronic Kidney Disease in a Large Taiwanese Population Follow-Up Study

Abstract: The global prevalence and incidence of chronic kidney disease (CKD) continue to increase. Whether hyperuricemia is an independent risk factor for renal progression and whether there are sex differences in the relationships between serum uric acid (UA) and a decline in renal function are unclear. Therefore, in this longitudinal study, we aimed to explore these relationships in a large cohort of around 27,000 Taiwanese participants in the Taiwan Biobank (TWB), and also to identify serum UA cutoff levels in men a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Metabolic changes during the menopause may lead to increased SUA levels in women [ 37 ], and epidemiological studies have also shown a positive association between SUA and insulin resistance in older women, but not in men [ 38 ]. Consistent with this gender difference, many studies have found that serum uric acid levels are more strongly associated with disease in women, including chronic kidney disease [ 39 ] and coronary heart disease [ 37 ]. More research is needed into the sex-specific role of β -cells function in HUA.…”
Section: Discussionmentioning
confidence: 93%
“…Metabolic changes during the menopause may lead to increased SUA levels in women [ 37 ], and epidemiological studies have also shown a positive association between SUA and insulin resistance in older women, but not in men [ 38 ]. Consistent with this gender difference, many studies have found that serum uric acid levels are more strongly associated with disease in women, including chronic kidney disease [ 39 ] and coronary heart disease [ 37 ]. More research is needed into the sex-specific role of β -cells function in HUA.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies indicated that elevated serum UA was an independent predictor for the development of CKD. 31 The underlying mechanism between UA and CKD risk are as follows: (1) UA induces hypertension by affecting endothelial function and reducing nitric oxide production; 32 (2) hyperuricemia triggers the activation of the renin-angiotensin-aldosterone system, leading to renal vasoconstriction and reduced renal plasma flow; 33 (3) UA may increase oxidative stress, leading to mitochondrial dysfunction, over-secretion of proinflammatory cytokines, and proliferation of vascular smooth muscle cells; 6 and (4) UA crystals can cause tubular damage through inflammation mediated by direct physical mechanisms. 6 Diet has also been implicated in the risk of CKD 25,34 and hyperuricemia.…”
Section: Discussionmentioning
confidence: 99%
“…A separate significant finding worth noting was that the association between hyperuricemia and the new onset of CKD in males was relatively stronger than that in females, with the adjusted HR of hyperuricemia for CKD being 1.925 (1.724–2.150) and 1.676 (1.530–1.848) for males and females, respectively. Previous studies have investigated sex differences in the correlations between hyperuricemia and incident CKD but obtained mixed results [ 13 , 42 , 43 ]. Estrogen is the most commonly considered reason for this sex difference, as it can cause the excretion of urate through urine [ 44 ] and inhibit the generation of uric acid by xanthine oxidase [ 45 ].…”
Section: Discussionmentioning
confidence: 99%